Flypaper effect: Analysis of financial transfers from the central government to provincial regions in Indonesia - Retno Fitrianti; Mirzalina Zaenal; Sanusi Fattah; Nurul Hidayah (Public and Municipal Finance, 2025)
This paper aims to analyze the influence of local revenues, unconditional grants, and total population on regional expenditure in six provinces in Sulawesi, Indonesia. Panel data covering the period from 2013 to 2023 were analyzed using the fixed effects model (FEM) using the STATA software. The results show that local revenue has a significant positive effect on regional expenditure (β = 0.366; p-value 0.000 < 0.05), unconditional grant has a significant positive effect on regional expenditure (β = 0.501; p-value 0.000 < 0.05), and total population has a significant positive effect on regional expenditure (β = 1.207; p-value 0.001 < 0.05). The results show considerable regional disparities, with Southeast Sulawesi and North Sulawesi displaying the highest dependency on central funds, while South Sulawesi exhibits relatively greater fiscal independence. These findings highlight the need for policy reforms to strengthen local revenue generation, minimize reliance on central government transfers, and prioritize investments in infrastructure. Such strategies are crucial for ensuring fiscal sustainability, enhanced local autonomy, and long-term regional growth.